Enhanced Microwave Absorption Performance in Sr-Modified La2NiO4±δ Nickelate With High Dielectric Loss - Liu, Sheng; Cheng, Yulan; He, Jun; Yan, Shuoqing; Luo, Heng; Deng, Lianwen (Frontiers in Materials, 2020)
This work aims to achieve the excellent microwave absorption in layered dielectric nickelate compounds. The phase, microstructure, electromagnetic properties and microwave absorption of the Sr modified La2-xSrxNiO4±δ (x=0, 0.3, 0.5, 0.75) nickelates were investigated, determining the analysis of the role of Sr doping level. All compounds reveal the single tetragonal phase identified as I4/mmm space group and the lattice parameters correlates with the doping content, evidencing by Rietveld refinement. By introducing the strontium, the pronouncedly increased electronic conductivity contributes the high dielectric loss, which gives rise to superior attenuation ability and absorbing bandwidth. A minimum reflection loss of −21.07 dB was found in La2-xSrxNiO4±δ (x=0.75) at the thickness of 1.9 mm, covering the effective bandwidth of 2.9 GHz. This enhanced microwave absorbing performance in nickelate hold promises in radar absorbing field.